Transcriptional profiles in bursal B-lymphoid DT40 cells infected with very virulent infectious bursal disease virus - Quan, Rong (Virol J, 2017)
BACKGROUND: Infectious bursal disease virus (IBDV) causes a highly contagious, immunosuppressive disease in chickens. The virus mainly infects immature B lymphocytes in the bursa of Fabricius (BF). Chicken B cell line DT40, an avian leukosis virus-induced B cell line, supports very virulent IBDV (vvIBDV) infection in vitro and thereby serves as a good model for investigating the infection and pathogenesis of this virus. However, a transcriptome-wide understanding of the interaction between vvIBDV and B cells has not yet been achieved. This study aimed to employ time-course DNA microarrays to investigate gene expression patterns in DT40 cells after infection with vvIBDV strain LX. RESULTS: DT40 cells infected with vvIBDV exhibited alterations in the expression of many important host genes involved in signal transduction pathways, including MAPK signaling, PI3K/mTOR signaling, cell death and survival, BCR signaling, and antigen presentation. The changes in cellular mRNA levels identified by microarray analysis were confirmed for 8 selected genes using real-time reverse transcription-PCR. The upregulation of inflammatory cytokines and Toll-like receptors (TLRs) in the bursa of vvIBDV-infected chickens might involve excessive activation of the innate immune and inflammatory responses and contribute to tissue damage. CONCLUSIONS: The present study is the first to provide a comprehensive differential transcriptional profile of cultured DT40 cells in response to vvIBDV infection and further extends our understanding of the molecular mechanisms underlying vvIBDV infection and pathogenesis.